Elements for Regulating Surrogacy Arrangements with Cross-border Effects - Bordaš, Bernadet (Zbornik radova Pravnog fakulteta u Novom Sadu, 2014)
Numerous cases of international surrogacy arrangements and their legal effects in different national legal frameworks have caused a need to weigh the possibility and necessity of regulating the issue on international level . The Hague Conference on Private International Law has been since 2011 involved in preliminary research activities of the issue, on the basis of which it will submit a final report in 2014 on the state of play and on the need to start drafting an international instrument. During the past three years two preliminary reports and four questionnaires have been submitted. Questionnaire 1 have been sent to the member states of the Conference and to other interested countries to collect data on crucial issues of surrogacy and its legal regulation in national legislations. Serbian law de lege lata prohibits surrogacy arrangements, but the 2011 Draft Civil Code introduces it to the domestic legal system as a tool of biomedically assisted fertilization. The present paper suggests that the regulation of surrogacy must also include surrogacy arrangements with cross-border effects for the sake of comprehensiveness of the future legal act on the issue. For this purpose, the paper indicates – based on the preliminary research conducted by the Hague Conference on Private International Law – those elements that should be included in future legislation of Serbia.